Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai pada Badan Layanan Umum (BLU) Pusat Veteriner Farma - Heny Devita Sari; Pompong Budi Setiadi; Sri Rahayu (Journal on Education, 2023)
Research purposes intended to test and analyze the influence of competence, discipline work simultaneously and partial against the employee performance. The methodology descriptive quantitative. Testing statistics in research using analysis linear regression multiple. The number of respondents 32 civil servants in a public service Veteriner Farma Center. Samples taken of the population target to technique data collection wearing e-questionnaire. The result showed that competence in partial will not affect performance, discipline influential strong work on performance. Simultaneously competence and discipline work impact on the employee performance.